The generational brain: Introduction. (October 2016) - Lux, Vanessa; van Ommen, Clifford
In contemporary society, the image of the "flexible brain" and the notion of neuroplasticity are increasingly replacing that of the static mature brain. Brains and neurons are considered to be constantly generated and regenerated. Age cohort comparisons and longitudinal studies introduce a developmental perspective to the field. However, these articulations and investigations occur within a sociopolitical field marked by vested interests and the celebration of all things neural. Utilizing the notion of "the generational brain, " we propose that it is fruitful to exploit the polysemity of the word "generation, " as well as the historicity of scientific concepts and methods, to interrogate and re/formulate questions currently addressed in developmental neuroscience in particular and neuroscience in general. This special issue's contributions provide an early impression of what a "critical friendship" with developmental neuroscience, aware of its sociocultural and epistemological implications as well as the historicity of concepts, may look like.